Filantropi Kreatif: Pemberdayaan Ekonomi Umat Berbasis Zakat Produktif pada Program 1000 UMKM Lazismu Kabupaten Pekalongan - Nur Kholidah; Ayesha Nur Salma (Cakrawala: Jurnal Studi Islam, 2019)
This study aims to find out how the mechanism, impact, supporting factors, and obstacles in implementing the community empowerment based on productive zakat in 1000 MSME’s programs. This research is field research using a descriptive qualitative approach. The subject of this research was Lazismu management and the mustahik. This study found that the 1000 MSME’s program was instrumental in helping MSME’s who had difficulty in developing their businesses. The assistance process is important in the success of the empowerment program. The impact of this program is an increase in business results, family income, abilities, knowledge, and skills as well as increased religious knowledge. Supporting factors for this program include the collaboration with Aisiyah institutions to provide assistance to the mustahik. While the constraints faced are not yet optimal implementation of SOPs and the lack of reporting and documentation of 1000 MSME programs